Studi Kejadian Ikutan Pasca Imunisasi (KIPI) Vaksin Covid-19 Pada Pelajar Di Wilayah Kerja Puskesmas Bojong I - Jamaludin Al Jamaludin Efendi; Sukma Eka Fitria (Pena Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
The vaccination program that was intensified by the government for students aged 16-18 years aims to support the preparation for the implementation of limited Face-to-face Learning (PTM) in the regions. Although the vaccines used in Indonesia in the national immunization program are declared safe and effective, there is no single type of vaccine that is guaranteed to be free of side effects or AEFI (Post Immunization Adverse Events). Therefore, this study is being conducted to find out whether there are AEFIs that occur a lot in the Covid-19 vaccine in students in the Bojong I Health Center Work Area. This research method uses an observational analytic research method by collecting data using a questionnaire that has been tested for validity and reliability then data is collected from respondents via google form which is validated via whatsapp, after the data is obtained then univariate analysis is carried out with IBM SPSS version 25 Result : The results showed that there were 135 students who lived in the working area of the Bojong I Health Center aged 16-18 years who had received a phase 2 vaccine dose. The most common AEFIs were muscle pain with the first order occurring in the Moderna vaccine as many as 14 students with 63.63% , the two Pfizer vaccines were 6 students with 42.85%, the three Sinovac vaccines were 32 students with 36.78%, and finally the AstraZeneca vaccine was 14 students with 33.33%, the most common AEFI that occurred next was weakness/sluggishness with the first order occurred in the Moderna vaccine as many as 11 students with 50%, the second Sinovac vaccine with 35 students with 40.22%, the third Pfizer with 5 students with 35.71%, and finally AstraZeneca with 2 students 16.66%.